2014
DOI: 10.1089/nat.2014.0495
|View full text |Cite
|
Sign up to set email alerts
|

A Single Dose of EGLN1 siRNA Yields Increased Erythropoiesis in Nonhuman Primates

Abstract: Decreased production of erythropoietin (EPO) causes anemia in patients with chronic kidney disease, and recombinant human EPO is used to treat renal failure associated anemia. The liver, the main EPO-producing organ in utero, maintains the capacity to produce EPO in the adult but in insufficient quantities to restore hemoglobin levels to normal in patients with impaired renal function. Inhibition of prolyl-4-hydroxylase domain (PHD) proteins is known to cause an increase in EPO production through its effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
1
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
(52 reference statements)
1
1
0
Order By: Relevance
“… Indeed, Minamishima and Kaelin have shown that liver-selective deletion of PHD1/2/3 in mice resulted in increased serum EPO levels that paralleled the mRNA levels in liver and exceeded those achieved by renal PHD2 knockout . Consistent with the hypothesis, liver-selective knockdown with PHD2 siRNA in rhesus led to clinically relevant increases in hemoglobin . In addition, we have demonstrated that a systemic HIF-PHD inhibitor (HIF-PHDi) had increased systolic PAP (sPAP) in a dose-dependent manner in a telemetered rat model (see Figure ).…”
supporting
confidence: 77%
See 1 more Smart Citation
“… Indeed, Minamishima and Kaelin have shown that liver-selective deletion of PHD1/2/3 in mice resulted in increased serum EPO levels that paralleled the mRNA levels in liver and exceeded those achieved by renal PHD2 knockout . Consistent with the hypothesis, liver-selective knockdown with PHD2 siRNA in rhesus led to clinically relevant increases in hemoglobin . In addition, we have demonstrated that a systemic HIF-PHD inhibitor (HIF-PHDi) had increased systolic PAP (sPAP) in a dose-dependent manner in a telemetered rat model (see Figure ).…”
supporting
confidence: 77%
“…20 Consistent with the hypothesis, liverselective knockdown with PHD2 siRNA in rhesus led to clinically relevant increases in hemoglobin. 21 In addition, we have demonstrated that a systemic HIF-PHD inhibitor (HIF-PHDi) had increased systolic PAP (sPAP) in a dose-dependent manner in a telemetered rat model (see Figure 2). 22 With this supporting evidence in mind, we undertook a discovery effort to identify a hepatoselective HIF-PHD inhibitor.…”
mentioning
confidence: 95%